Invisible valley [videorecording (DVD)] - Ruiz, Raul (Kino Lorber, 2022)
Weaves together the disparate stories of undocumented farmworkers, wealthy snowbirds, and music festival-goers over the course of a year in California's Coachella Valley. In exploring the Valley's history as well its imperiled future, this riveting documentary uncovers an imminent environmental and social crisis, and the looming consequences for the people who call it home.